Littoral Cell Angioma of the Spleen: A Case Report and Review of Diagnostic Considerations - Serkan Demir; Faruk Yazıcı; Muhammed Salih Süer; Çiğdem Sercan; Turgay Sayın (Academic Journal of Health, 2026)
Background: Littoral cell angioma (LCA) is a rare vascular tumor of the spleen arising from littoral cells that exhibit combined endothelial–histiocytic differentiation and line the red-pulp sinusoids. Because clinical manifestations and imaging characteristics are nonspecific, definitive diagnosis typically requires histopathology supported by immunohistochemistry demonstrating this dual lineage. Case: A 52-year-old man presented with a 3–4-month history of persistent left upper-quadrant pain. Ultrasonography, contrast-enhanced CT, and multiparametric MRI identified a solitary splenic mass with heterogeneous T2 hyperintensity and contrast-enhancement kinetics paralleling native splenic parenchyma, suggesting a vascular lesion. Following appropriate pre-splenectomy vaccination, laparoscopic splenectomy was performed without complications. Histopathologic examination revealed anastomosing cystic-vascular spaces lined by enlarged but cytologically bland littoral-type cells with no atypia, increased mitotic activity, or necrosis. Immunohistochemistry showed endothelial–histiocytic immunophenotype (CD31+, CD68+, Langerin+) with ERG−/CD34− staining, confirming LCA. The postoperative course was uneventful. Oral intake resumed within 24 hours; the patient was discharged on postoperative day 4 and remained asymptomatic at follow-up with no evidence of recurrence. Conclusion: LCA should be included in the differential diagnosis of atypical splenic vascular masses. While cross-sectional imaging may raise suspicion, a definitive diagnosis hinges on radiologic–pathologic correlation and immunophenotypic confirmation of endothelial–histiocytic differentiation. In symptomatic, enlarging, or diagnostically indeterminate cases, splenectomy provides both tissue diagnosis and definitive treatment.